The Growth-Emissions Paradox: Assessing the Offset of Climate Mitigation by Economic Expansion in Ethiopia - Belay Sitotaw Goshu; Muhammad Ridwan (Britain International for Academic Research (BIAR-Publisher), 2026)
Ethiopia's climate mitigation initiatives from 2010 to 2023, under the Climate Resilient Green Economy (CRGE) framework, demonstrate a dual strategy of renewable energy expansion and afforestation, achieving modest offsets amid 8.4% average annual GDP growth. Total mitigation amounted to 34,006 tCO₂, with renewables contributing 49.3%, driven by hydropower surging to 85% of electricity generation by 2022, phasing out 95% of fossil fuels, and afforestation accounting for 50.7%, via 3,450 kHa planted and a 25.6% forest cover increase, sequestering 500 tCO₂ annually. However, a -3.4 kHa/year afforestation slope and low overall impact (2% of national emissions) highlight scalability challenges. Sectoral greenhouse gas emissions rose 196% to 770 ktCO₂e, with agriculture's share declining from 77% to 32%, overtaken by industry (39%) and transport (26%). Emissions growth was driven primarily by transport activity (46.2% contribution; feature importance 0.176) and industrial GDP (38.1%; 0.129), while the energy sector’s –7.1% offset underscores the efficacy of renewable deployment. Intensity halved across sectors, yielding absolute decoupling in agriculture (0.9 indexes) and industry (0.8), though transport recoupled sharply. Decoupling analysis confirms full relative decoupling over the 13 years, with emissions rising only 4.0, lagging GDP growth, and producing a 41.3% reduction in intensity (–15.948 tCO₂ per million USD per year). Periodically, 2010-2015 achieved a -26.1% intensity drop foundational to CRGE, while 2016-2023 sustained -17.7% amid a 39.8% emissions rise, averting 117,426 ktCO₂ (4.2% effectiveness). Net effects balanced 184.0% GDP expansion with 67.6% offsets, closing a 0.36 efficiency gap. These findings affirm Ethiopia's positive low-carbon trajectory, economic decoupling, balanced mitigation drivers, positioning it as an African exemplar. Yet vulnerabilities such as drought exposure, urbanization pressures, and equity gaps demand accelerated reforms to deliver NDC-aligned emissions cuts and net-zero by 2050.